East Africa Scenarios Workshop - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
The East Africa Strategic Futures Workshop was held in Arusha, Tanzania and hosted by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), in partnership with the Society for International Development and Panos Eastern Africa. Read a full summary of the workshop on our blog. All photos by Panos East Africa.